Entre a poética e a profecia: uma abordagem hermenêutica de Oseias 1,1-2,3 - Rocha, Matheus Eduardo de Oliveira (2022)
The present research analyzed the relationship between poetics and prophecy, through a hermeneutic approach to the text of Hosea 1,1 to 2,3. Because it is commonly interpreted in an androcentric perspective of religious normalization, its majority reception relates the male figure as a strict representation of divinity, to the point where the woman, her children, and the land they inhabit become a metaphor for sin and apostasy. In this way, the work had as primary objective to make an approach to this prophetic report that would perceive Other latente meanings, freeing it from its interpretive enclosure. Therefore, it was necessary to understand this text as a “being of language”, a detailed study of its structure and its interactions with the historical-social dynamics, as well as an opening to the semantic multivocality of its poetic configuration. Thus, it was presented the intertwining between poetics, hermeneutics and prophecy, based on contributions from the thought of Paul Ricoeur. Therefore, the relationship between poetics and religious experience, the intersection between hermeneutics, biblical texts and the conceptualization of literary were analyzed, as well as, in what all this results for a vision of prophetism as poetics that launches itself to further meanings, but which is rooted in the community concreteness. Afterwards, the search focused on the exegetical analysis of the pericope of Hosea 1,1 to 2,3, to which it engaged in the exercise of its translation, study and indication of its structure, examination of the philological and semantic dimensions of the verses, elaboration of comments about them, just like in the investigation about the reality and the social tensions that guided the writing process. Finally, the work covered the hermeneutic movement of giving voice to the figures and characters so often obliterated in the reading of the text. Accordingly, attention was paid to the potentiality that is carried in the poetic configuration of the prostitution of the land, of Gômer and his sons Jezreel, Lo Ruhamah and Lo Ammi, offering the possibility of perceiving the multiplicity of testimonies of religious experiences present in the literary record of Hosea. From this perspective, the research opend up to the diversity of meanings that are shown in the bodies and images of the narrative, testifying that, at the same time that it touches on the concreteness of the sufferings of its time, it gives rise to hope for liberation in the prophetic force. (AU)